Population-level impact of information sources on HIV testing uptake in South Africa: gender and age disparities. (July 2019) - Wand, Handan; Reddy, Tarylee
In South Africa, mass media and interpersonal communication sources have been used extensively to increase awareness of human immunodeficiency virus (HIV)/AIDS. A sub-population of 10, 565 black Africans who participated in the 2011–2012 household survey was analysed. Overall compared to men, a higher proportion of women had ever been tested for HIV (76% versus 60%). In age-specific analysis, men and women aged 25–49 years were more likely to be ever been tested compared to the youngest (<25 years) and the oldest age groups (50+ years). More than 80% of the study population was exposed to mass media tools, while exposure to interpersonal information sources was less common (16–72%). Among adolescents, 37% (men) and 41% (women) of the HIV tests were collectively associated with exposure to interpersonal programmes, while mass media tools had substantial contributions on HIV testing rates among the older individuals. Information sources to promote HIV/AIDS awareness should be tailored to reduce age–gender disparities.